Advances in the morphosyntactic description of transitivity in the Asháninka of the upper Perené - Alonzo Sutta, Alicia (2021)
The traditional view of transitivity is based on the fact that the language has both transitive and intransitive verbs. On this basis, in transitive clauses there is an action of transference from a subject to an object. According to this statement, the transitive verb is the one that denotes events about the object, either an action on it or a change of state of it. However, studies subsequent to this perspective, carried out by Hopper and Thompson (1980) disagree with the above and propose that transitivity does not respond to a simple transference from the subject to the object. For the authors, transitivity is a property of languages characterized by the fulfillment of certain parameters, which indicate the greater or lesser degree of transitivity of clauses within a discursive context. The present study aims to describe the morphosyntactic characteristics that show a higher degree of transitivity in the clauses of Upper Perene Asháninka.